Effects of Different Extraction Conditions on The Production of Anthraquinone - Nurul Ain, J.; Mimi Sakinah, A. M.; Zularisam, A. W. (AENSI Publishing, 2016)
Natural dyes have been used for the coloring of textiles since pre-historic times. Nowadays, there is an increased of interest in natural dyes as the replacement of synthetic dyes due to general environmental awareness and the increase of public interest in natural products. Morinda citrifolia (mengkudu) was used as the source of natural dye in this study. The extracted compound from the roots of Morinda citrifolia is known as anthraquinone (alizarin) that gives a red color for potential textile application. This study was performed to investigate the effects of solid liquid ratio (SLR) (1:100 to 5:100), extraction time (up to 10 hours), and pH (1 to 11) on the concentration of anthraquinone. The anthraquinone extract was analyzed by using a UV-Vis spectrophotometer. The best condition to extract anthraquinone from Morinda citrifolia roots was at 1:400, 2 hours, and pH 7 of SLR, extraction times, and pH, respectively. The study proved that Morinda citrifolia can produce a natural dye that has a strong color which can be used in textile industries.